The Relationship Between Organizational jJustice and Nurses' Job Embeddedness in Teaching Hospitals - Fatemeh Rakhshani Zabol; Omolbanin Akbari; Seyyed Abolfazl Vagharseyyedin; Zahra Farajzadeh (Hamadan University of Medical Sciences, 2019)
Introduction: Severe nurse shortages and their turnover have made researchers focused on identifying the factors affecting the retention of nurses and relationships between these factors. The aim of this study was to investigate the relationship between organizational justice and Nurses' job embeddedness in Teaching Hospitals. Methods: In this descriptive-analytical study, data was collected from 215 nurses working in two educational hospitals in city of Birjand who were selected by stratified random sampling. Crossley et al Global Job Embeddedness Scale and Niehoff and Moorman's Organizational Justice Scales were used to measure the studied variables. Data was analyzed by SPSS 16 using independent t-test, one way ANOVA, Tukey's post-hoc test, Pearson's correlation coefficient and multiple regression analysis at a significance level less than 0.05. Results: Based on the results, the level of job embeddedness of nurses was higher than the average (3.05±1.07), and men had more embeddedness than women. In this study, from dimensions of organizational justice, the dimensions of interactional justice showed the highest correlation with job embeddedness. Multiple regression analysis showed that interactional justice and distributive justice predicted 34.6% of changes in job embeddedness (F=37.20, P<0.001), and interactional justice was a better predictor of job embeddedness compared to distributive justice. Conclusion: The results demonstrated the necessity of implementing programs to improve the Nurses' job embeddedness, especially female nurses, through increasing the perceived organizational justice, especially the dimensions of interactional justice and distributive justice.